Time perception in mild cognitive impairment: interval length and subjective passage of time - Coelho, Sara (2017)
Objectives Patients with mild cognitive impairment (MCI) may have difficulties in time perception, which in turn might contribute to some of their symptoms, especially memory deficits. The aim of this study was to evaluate perception of interval length and subjective passage of time in MCI patients as compared to healthy controls. Methods Fifty-five MCI patients and 57 healthy controls underwent an experimental protocol for time perception on interval length, a questionnaire for the subjective passage of time and a neuropsychological evaluation. Results MCI patients presented no changes in the perception of interval length. However, for MCI patients, time seemed to pass more slowly than it did for controls. This experience was significantly correlated with memory deficits but not with performance in executive tests, nor with complaints of depression or anxiety. Conclusions Memory deficits do not affect the perception of interval length, but are associated with alterations in the subjective passage of time.